Heloise and Abelard - Gilson, Etienne Henry, 1884 (Ann Arbor : University of Michigan Press, 1972)
Translation of Heloise et Abelard
Includes appendix and notes.
Keywords: Abailard, Pierre, 1079-1142; Heloise, 1101-1164